Military Power in Europe - Freedman, Lawrence. author. aut Link
XVII, 241 p.
Keywords: These essays illuminate different aspects of military power and European security. It deals with the practicalities of planning and command within an alliance structure or the problems connected and with distinguishing between offensive and defensive operations for purposes of arms control.